Pengaruh Tren Fashion dan Brand Image terhadap Hijab Remaja - Berta Melati A.C; Acep Samsudin; Rusdi Hidayat; Naufal Azani P.R; Syahrul Dwi K; Muhammad Fathin R; Nanda Nadia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Fashion and clothing style is one of the most basic everyday human needs. Clothing is not only a necessity, but also reflects the lifestyle of a particular group of people and expresses their true personality and identity. may be affected. The purpose of this study is to explain the influence of fashion trends and brand image on young people's preferences for hijabs. It is intended for This research uses the library survey method or library survey. Some of the results of this study indicate that the influence of fashion trends and brand image on young people's headscarf preferences is a powerful tool for young consumers' self-expression and shopping needs. Keywords: Preferences, Brand Images, Fashion Trend, Hijab